Heteronuclear Efimov resonances in ultracold quantum gases - Ulmanis, Juris; Häfner, Stephan; Kuhnle, Eva; Weidemüller, Matthias (National Science Review, 2016)
Abstract. The Efimov scenario is a universal three-body effect addressing many areas of modern quantum physics. It plays an important role in the transition be